Simulation Analysis and Experimental Study on Strength Optimization of a Plug-In Oil Hose Joint - Chang Chen; Jikun Guo; Shifu Zhang; Qixin Zhang; Dongmei Zhang; Yongjie Niu; Hao Sun (Advances in Materials Science and Engineering)
A plug-in oil hose joint is used as the research object in this study. Aimed at the problem of pipeline breakage due to insufficient strength of the joint during the process of oil transportation on the sea, a three-dimensional geometric model of the joint is constructed according to the structural characteristics of the plug-in joint. The mechanical properties of the plug-in hose joint were studied by numerical simulations and field experiments. The strength of the joint was optimized by applying materials with different properties and adjusting the circular angle of the joint. The tensile strength test results of the plug-in oil hose joint are consistent with the theoretical analysis, which shows that the method proposed in this paper can effectively improve the tensile strength of the oil hose joint. It is of great significance to expand the scope of the plug-in connector and ensure the safe and stable use of the hose system.